2015
DOI: 10.5455/medarh.2015.69.307-310
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Markers and Procoagulants in Chronic Renal Disease Stages 1-4

Abstract: Introduction:Starting from the point that the chronic kidney disease (CKD) is chronic, inflammatory and hypercoagulable state characterized by an increase in procoagulant and inflammatory markers high cardiovascular morbidity and mortality in these patients could be explained.Aim:The aim of the research was to monitor inflammatory markers and procoagulants in various stages of kidney disease (stage 1-4).Materials and Methods:The research included 120 subjects older than 18 years with CKD stages 1-4 examined an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 12 publications
1
15
0
2
Order By: Relevance
“…The outcome differs in different HD therapies, with more significant outcomes in HDF and HP than in HD. CRF is a chronic condition characterized by inflammation, and hypercoagulability, meaning patients will have increased levels of procoagulant and inflammatory markers . In CRF patients that had undergone HD, a transient decrease in CD40L and CD62P was detected .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome differs in different HD therapies, with more significant outcomes in HDF and HP than in HD. CRF is a chronic condition characterized by inflammation, and hypercoagulability, meaning patients will have increased levels of procoagulant and inflammatory markers . In CRF patients that had undergone HD, a transient decrease in CD40L and CD62P was detected .…”
Section: Discussionmentioning
confidence: 99%
“…CRF is a chronic condition characterized by inflammation, and hypercoagulability, meaning patients will have increased levels of procoagulant and inflammatory markers. 38 In CRF patients that had undergone HD, a transient decrease in CD40L and CD62P was detected. 39 CD62P, as an indicator of platelet degranulation when expressed on platelet surface, plays a mediate role in the interactions of platelet and leukocyte cells, which can stimulate the production of chemoattractants and growth factors.…”
Section: Decreased Expression Of Cd62p and P10 And Increased Expresmentioning
confidence: 94%
“…The inflammatory biomarkers, C-reactive protein (CRP), interleukin (IL)-6 and tumor necrosis factor (TNF)-α, have been reported to be enhanced in CKD [2,29] Renal Insufficiency Cohort (CRIC) study, the inflammatory biomarkers IL-1β, IL-1 receptor antagonist, IL-6, TNF-α, CRP and fibrinogen, are correlated negatively with markers of kidney function, and positively with albuminuria [30]. A cytokine and a T cell imbalance have been also reported in ESRD [31].…”
Section: Chronic Kidney Disease and Inflammationmentioning
confidence: 99%
“…Inflammation is a common feature in CKD, especially enhanced in ESRD patients on hemodialysis (HD). This chronic inflammatory state seems to contribute to aggravate kidney dysfunction and favor the occurrence of comorbidities and the risk of mortality [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…This type of vascular access is more prone to infection or inflammation, and thus, it might be associated with poor outcome of HD patients. Markers of inflammation, such as C-reactive protein (CRP) [26] and inflammatory cytokines [27], are raised in CKD patients, particularly in HD patients. In a recent study by our team, we found that CRP, malnutrition and the use of CVC were independent risk factors for mortality in HD Some uremic toxins express potent pro-inflammatory and oxidative activity [29], contributing to amplify inflammation and oxidative injuries to cells and plasma constituents.…”
Section: Anemia and Inflammationmentioning
confidence: 99%